FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PROFESI GURU MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN (S1) JURUSAN TEKNIK SIPIL FT UNP - 957-976 , Arif Firman Alim (CIVED, 2016)
ABSTRAK The study program of Technical Education Building Department of Civil Engineering, Faculty of Engineering, Padang State University is a program of study that prepares students to become professional workers in the field of vocational education. Graduates of Technical Education Building Program can be expected natinya prospective teachers Vocational High School of Technology and Engineering  Education  Building  Techniques.  Based  on  the  interviews  and  the results  of  previous  studies  it  is  known  that  students  are  not  interested  in  the teaching  profession.  To  determine  the  factors  that  affect  the  interests  of  the teaching profession, the authors conducted a study with the title: Factors Affecting Student Interests Professional Teacher Education Program Building Engineering Department of Civil Engineering Faculty of Engineering, Padang State University. This research is descriptive. The study population is students of Technical Education Building Department of Civil Engineering, Faculty of Engineering, Padang  State  University  year  in  2014.  The  sampling  technique  used  total sampling method with a total sample of 68 respondents. The instrument used for data collection was a questionnaire study. Data analysis technique used is descriptive statistical analysis techniques with percentage calculations. The  results  of  this  research,  there  are  five  sub-indicators  of  internal factors that affect the interests of the teaching profession that is emotional, perception, motivation, talent and mastery of science. Of the five sub-indicators of the talent factor is the internal factors that most influence. Factors influential talents of 25.41% interest in the teaching profession to students of Technical Education Building Department of Civil Engineering Faculty of Engineering, Padang State University year in 2014.   Keywords: internal factors, interest, teaching profession